Performance Comparison of Managed C# and Delphi Prism in Visual Studio and Unmanaged Delphi 2009 and C++ Builder 2009 Languages - Karaci, Abdulkadir (Foundation of Computer Science, 2011)
anaged C# and Delphi Prism in Visual Studio 2008 and Unmanaged Delphi 2009 and C++ Builder 2009 programming languages are increasingly gaining in popularity. In this study, response times of these languages, memory consumptions and code lengths were tested with various work loads and the results belonging to these tests were given. Whether there was a significant difference among the data obtained by the test results was tested by using Friedman test and a significant difference was found. Also, the differences between managed languages and unmanaged languages were revealed by the results of the performance test. KeywordsTest, Programming Language, C#, Delphi, M anaged, Unmanaged.